Development of a bead-based suspension array for the detection of pathogens in acute respiratory tract infections. Issue 14 (August 2016) - Chen, Yu-Sheng; Li, Hong-Ru; Zhang, Wei; Hua, Zhi-Dan; Lin, Xiao-Hong; Lin, Meng-Qing; Huang, Wen-Sen; Huang, Li-Ping; Yu, Xiao-Li; Xu, Neng-Luan; Lin, Ming; Xie, Bao-Song; et al.
We developed a high-throughput bead-based suspension array for simultaneous detection of 20 respiratory tract pathogens in clinical specimens. Pathogen-specific genes were amplified and hybridized to probes coupled to carboxyl-encoded microspheres. Fluorescence intensities generated via the binding of phycoerythrin-conjugated streptavidin with biotin-labeled targets were measured by the Luminex 100 bead-based suspension array system. The bead-based suspension array detected bacteria in a significantly higher number of samples compared to the conventional culture. There was no significant difference in the detection rate of atypical pathogensatypical pathogens or viruses between the bead-based suspension array and real-time PCR. This technology can play a significant role in screening patients with pneumonia.